Beyond Capacity Limitations II: Effects of Lexical Processes on Word Recall in Verbal Working Memory Tasks in Children With and Without Specific Language Impairment. - Mainela-Arnold, Elina; Evans, Julia L.; Coady, Jeffry (Journal of Speech, Language & Hearing Research, 2010)
Purpose: This study investigated the impact of lexical processes on target word recall in sentence span tasks in children with and without specific language impairment (SLI). Method: Participants were 42 children (ages 8;2-12;3 [years; months]): 21 with SLI and 21 typically developing peers matched on age and nonverbal IQ. Children completed a sentence span task in which target words to be recalled varied in word frequency and neighborhood density. Two measures of lexical processes were examined: the number of nontarget competitor words activated during a gating task (lexical cohort competition) and word definitions. Results: Neighborhood density had no effect on word recall for either group. However, both groups recalled significantly more high- than low-frequency words. Lexical cohort competition and specificity of semantic representations accounted for unique variance in the number of target word recalled in the SLI and chronological age-matched (CA) groups combined. Conclusions: Performance on verbal working memory span tasks for both SLI and CA children is influenced by word frequency, lexical cohorts, and semantic representations. Future studies need to examine the extent to which verbal working memory capacity is a cognitive construct independent of extant language knowledge representations. Reprinted by permission of the publisher.